Standard Versus Arm-Length-Normalized Conditions for Assessment of the Closed Kinetic Chain Upper Extremity Stability Test in Healthy Youth Athletes - Katie Sloma; John Arvesen; Ava Davis; Ashley Erdman; Alex Loewen; Joshua Riesenberg; Henry Ellis; Philip Wilson; Sophia Ulman (International Journal of Sports Physical Therapy, 2026)
Background Criterion-based assessment of shoulder function includes screenings, such as the Closed Kinetic Chain Upper Extremity Stability Test (CKCUEST), to help identify deficits in stability, neuromuscular control, and proprioception. However, normative performance for the CKCUEST has been predominantly established in elite and collegiate athletes, and it has been shown that arm length, sex, and weight may influence performance. Purpose To compare performance and establish agreement between standard versus arm-length-normalized testing positions in adolescent athletes and establish population-specific reference values. Study Design Cross Sectional Methods Healthy athletes (ages 14-18 years) recruited from local teams, clubs, and youth sports organizations performed two conditions of the CKCUEST, standard and arm-length-normalized. Performance differences were evaluated using a Wilcoxon signed-rank test, with effect sizes ( r ), while agreement between conditions was assessed using intraclass correlation coefficients and Bland-Altman analysis. Spearman correlations were used to assess associations with participant demographics and Mann–Whitney U tests were performed to compare contact versus overhead athletes. Results One hundred fifty-four athletes (120 male, 16.5±1.2 years, 75.8±18.0 kg) participating in baseball, football, lacrosse, volleyball, basketball, water polo, and tennis were included for analysis. Performance was greater on the arm-length-normalized condition (standard: 23.0±5.8 taps; normalized: 23.9±5.5 taps, p